2016
DOI: 10.1177/0954406216650473
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of a dual quadruped vehicle based on whole close-chain mechanism

Abstract: A new ''whole close-chain mechanism'' concept is proposed for the design of the modular legged unit of walking vehicles. Based on this concept, the walking vehicle called dual quadruped vehicle is developed and constructed. The vehicle designed as an omnidirectional carrying platform contains two identical single-driven quadruped mechanisms. The details of the design procedure are given, including the single close-chain legged mechanism, the modular legged unit, and the dual quadruped vehicle. The construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…According to the characteristics of the topological structure 27 and the creative mechanism design method 28 of the planar kinematic chain, we proposed the single close-chain legged mechanism through the particularization of the feasible specialized chain. The full-pivot legged mechanism with bionic characteristics is shown in Figure 2.…”
Section: Structure Analysis and Mechanism Designmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the characteristics of the topological structure 27 and the creative mechanism design method 28 of the planar kinematic chain, we proposed the single close-chain legged mechanism through the particularization of the feasible specialized chain. The full-pivot legged mechanism with bionic characteristics is shown in Figure 2.…”
Section: Structure Analysis and Mechanism Designmentioning
confidence: 99%
“…In consideration of these above-mentioned conditions, we provided five pre-assigned points (marked with circles in Figure 4) on the desired foot trajectory, and the x pi and y pi are x and y components of the pre-assigned points. The objective function is expressed as equation (3), and we obtained the optimal solutions using the sequence quadratic program 27 in Matlab™. The optimum values of the linkages are described in Table 1.…”
Section: Structure Analysis and Mechanism Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (2019) combined four groups of quadruped robots into a 16-legged platform, which can perform turning and other functions through the interaction of four motors. Wu et al (2017) analyzed the single leg structure by using the closed-vector method and optimized the parameters of the single leg structure. Then they studied a fully closed leg device and walking vehicle and produced the detailed design process of a single, closed-loop leg mechanism, a modular leg unit and a double quadruped robot (Wu and Yao, 2018a;Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At present, researches on single-DOF closed-loop mechanism are mainly focused on leg mechanism and gripper mechanism [ 20 ]. Studies of closed-loop planar mechanisms such as Chebyshev Mechanism [ 21 ], Klann Mechanism [22], LARM BiPED Mechanism [23] and DQV [24] have shown that the closed-loop series structure possesses the integral rigidity, more suitable for missions under a high load, and it performs better at high stride frequency [25,26].Liu [27] designed a single DOF robot leg mechanism intended for tailed quadruped locomotion.…”
Section: Introductionmentioning
confidence: 99%